Sodium-ion battery high-entropy layered positive electrode material and preparation method and application thereof

By doping multiple elements and adjusting the ratio, a high-entropy layered cathode material was prepared, which solved the problems of phase change and structural expansion of the cathode material of sodium ion battery during charging and discharge, and achieved excellent cyclic stability and electrochemical performance.

CN119764440APending Publication Date: 2025-04-04SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411968966.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The positive electrode material of sodium ion battery is prone to irreversible phase change and structural expansion during charging and discharging, affecting its cycling performance.

Method used

By doping elements such as Ni, Fe, Mn, Zn, Cu, etc., their ratio is adjusted to prepare a high-entropy layered positive electrode material to inhibit the slippage of the transition metal layer during sodium ion deintercalation, and improve the stability of the material and the diffusion ability of Na+.

Benefits of technology

The excellent cycle stability and electrochemical performance of the cathode material of sodium ion battery are achieved, reducing the cost and environmental impact of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764440A_ABST
    Figure CN119764440A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium-ion battery high-entropy layered positive electrode material and a preparation method and application thereof, the sodium-ion battery high-entropy layered positive electrode material has good electrochemical performance by regulating the ratio of Ni, Fe, Mn, Zn and Cu, especially has excellent cycle performance, and overcomes the defect of instability of a sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion battery materials, and specifically relates to a sodium ion battery high entropy layered positive electrode material, and also relates to a preparation method of the sodium ion battery high entropy layered positive electrode material and an application of the sodium ion battery high entropy layered positive electrode material as a sodium ion battery high entropy layered positive electrode material. Background Art

[0002] In recent years, with the large-scale application of lithium-ion batteries, the cost of lithium-ion batteries has gradually increased due to the uneven distribution of lithium resources and high prices. Sodium, which has similar chemical properties to lithium, is one of the most abundant elements on Earth. It is cheap and has a suitable redox couple. Therefore, sodium-ion batteries (SIBs), which have similar working principles to lithium-ion batteries and are abundant in resources, have received widespread attention and are considered to be low-cost alternatives to lithium-ion batteries. They will play a vital role in solving energy crises and coping with lithium ore resource depletion. They are extremely valuable energy storage devices. However, the disadvantages of SIBs are also obvious, such as low coulomb efficiency and severe volume expansion caused by a large radius (Na + 102pm vs Li + 76pm) and low reversible capacity. Therefore, the development of SIBs electrode materials with high energy density, excellent rate performance and excellent stability has become a hot topic in the current field of energy materials.

[0003] So far, different types of SIBs electrodes have been developed using carbonaceous materials, intermetallic alloys, organic compounds and TM oxides (or sulfides). Among them, the negative electrode materials can easily achieve high specific capacity (≥300mAh / g), while the positive electrode materials are usually in the range of 100-150mAh / g, which greatly limits the energy density. Therefore, the main challenge of developing SIBs positive electrode materials has become a top priority for researchers. Among the various positive electrode materials, layered TM oxides (NaxTMO2, TM=Fe, Mn, Ni, Co, Cr, Ti, V and their combinations) are regarded as candidate positive electrode materials for the next generation of high-performance sodium-ion batteries due to their high capacity, high rate performance and low cost.

[0004] However, due to Na + The ionic radius is much larger than that of Li +Due to the ionic radius of the layered TM oxide positive electrode, it needs to undergo complex electrochemical behaviors and structural evolution during the charge and discharge process. When sodium ions are embedded in the interlayer, the distance between atoms in the lattice needs to be adjusted to accommodate the new ions, which increases the lattice spacing of the material. However, in the process of extracting sodium ions, the lattice will shrink back to its original state or produce a certain degree of structural changes. Therefore, the deep (de)embedding of sodium ions can easily induce irreversible phase changes and inevitably cause large expansion and contraction of the lattice. In some cases, the phase change may be irreversible, which will change the original crystal structure of the material and affect the diffusion channel of sodium ions and the kinetic process of extracting and embedding. This problem is a problem that needs to be avoided during the charge and discharge cycle, and is one of the important factors affecting the cycle performance of layered metal oxides.

[0005] In recent years, multi-element co-doped high entropy oxidation cathode materials have provided a solution to the above problems. So far, by doping with Cu, Ti, Zn, Al and other elements to replace the layered material Na x One or several elements in TMO2 can usually improve the electronic structure of the material, reduce the Jahn-Teller effect, reduce the dissolution of transition metal ions, and inhibit phase changes during charge and discharge cycles. In addition, from a kinetic point of view, cation substitution may also accelerate the diffusion of electrons and sodium ions, thereby significantly improving the kinetic performance of the material during the cycle. Summary of the invention

[0006] In order to obtain a new type of sodium ion battery positive electrode material, the present invention provides a sodium ion battery high entropy layered positive electrode material, wherein the sodium ion battery high entropy layered positive electrode material is achieved by regulating the ratio of Ni, Fe, Mn, Zn and Cu elements to have good electrochemical properties, especially excellent cycle performance.

[0007] In a first aspect of the present invention, a sodium ion battery high entropy layered cathode material is provided, whose chemical formula is NaNi x Fe y Mn z Zn m Cu p O2, where 0 <x<1,0<y<1,0<z<1,0<m,p<0.1。

[0008] The high entropy layered cathode material for sodium ion batteries of the present invention is doped with a variety of elements, and the ratio of these elements is regulated to inhibit the slippage of the transition metal layer during the sodium ion deintercalation process, thereby improving the stability of the material and ensuring the Na + The normal diffusion makes the high entropy layered cathode material of the sodium ion battery of the present invention have excellent cycle stability.

[0009] Preferably, the high entropy layered cathode material for a sodium ion battery belongs to the hexagonal crystal system and has a space group of R-3m. Further preferably, the high entropy layered cathode material for a sodium ion battery is an O3 type layered structure with a space group of R-3m.

[0010] The structure of the high entropy layered cathode material for sodium ion batteries of the present invention is highly symmetrical. On the one hand, the hexagonal crystal system itself has a high symmetry. On the other hand, the space group R-3m further embodies a specific combination of symmetric elements on this basis. This high symmetry makes the physical properties of the crystal in all directions have a certain equivalence. In addition, the structure of the high entropy layered cathode material for sodium ion batteries of the present invention is also highly stable. The symmetry of the R-3m space group enables the atoms or ions in the crystal to be arranged in a stable manner. This stable structure helps to improve the thermodynamic stability of the crystal, so that it can maintain its crystal structure within a certain temperature and pressure range, and is not prone to phase change or decomposition. The high entropy layered cathode material for sodium ion batteries of the present invention regulates the physical properties of the R-3m space group crystal to a certain extent by doping with a small amount of transition metal elements, which helps to improve its stability to meet different application requirements.

[0011] In particular, the high-entropy layered cathode material for the sodium ion battery of the present invention is low-cost, non-toxic and harmless, environmentally friendly, and has good cycle stability when applied to sodium ion batteries.

[0012] In a second aspect of the present invention, a method for preparing the above-mentioned high entropy layered cathode material for sodium ion batteries is provided, which comprises the following steps:

[0013] S1. ball milling a sodium source, a nickel source, an iron source, a manganese source, a zinc source and a copper source under an inert atmosphere to obtain a first mixture precursor;

[0014] S2. heating the first mixture precursor obtained in step S1 for the first time to obtain a second mixture precursor;

[0015] S3. The second mixture precursor obtained in step S2 is heated for the first time to obtain a high-entropy layered positive electrode material for a sodium ion battery.

[0016] In the above method, the amount of the sodium source, nickel source, iron source, manganese source, zinc source and copper source is calculated according to the molar ratio of each metal element in the obtained sodium ion battery high entropy layered positive electrode material product, that is, the molar ratio of the sodium source, nickel source, iron source, manganese source, zinc source and copper source is the stoichiometric ratio of each raw material obtained according to each element in the final product, but in actual large-scale production, the amount of each raw material used can be determined according to the specific situation considering various factors such as loss, grade and characteristics of the raw materials, etc., as long as the chemical formula of the obtained sodium ion battery high entropy layered positive electrode material satisfies NaNi x Fe y Mnz Zn m Cu p O2 is sufficient, where 0 < x < 1, 0 < y < 1, 0 < z < 1, 0 < m, p < 0.1. Additionally, the implementation method of the ball milling is a conventional ball milling method in the art, such as tumbling ball milling, oscillating ball milling, grinding ball milling, and high-energy ball milling, etc.

[0017] Preferably, in the above method, the particle size of the first mixture precursor obtained in step S1 is less than 100 μm, preferably 50 - 80 μm, so that the raw materials can better contact, facilitating better diffusion of each raw material during the subsequent sintering process.

[0018] It should also be clear that after ball milling, sieving treatment can be carried out to screen out particles with too large particle size to ensure that the particle size of the first mixture precursor meets the requirements. Or the ball milling time can be extended to make the first mixture precursor meet the particle size requirements. Preferably, in the above method, the grinding balls used for ball milling are zirconium balls, tungsten carbide grinding balls, stainless steel balls, etc. The diameter of the grinding balls can be a conventional diameter in the art, such as 10 mm, 8 mm, 5 mm, etc., and the ball-to-material ratio can be (10 - 30):1.

[0019] Preferably, in the above method, the grinding balls used for ball milling need to be cleaned before use, such as using one or more of anhydrous ethanol, acetone, and isopropanol for cleaning. Specifically, it can be cleaned once or multiple times, such as 2 times, 3 times or more. After cleaning, drying is also required to remove the residual liquid on the surface. This cleaning can prevent impurities such as powder attached to the periphery of the grinding balls from affecting the raw materials and further affecting the performance of the product.

[0020] Preferably, in the above method, the ball milling process needs to be carried out under an inert gas, and the inert gas is one or more of high-purity nitrogen, argon, and helium. During the ball milling process, due to the huge energy inside the ball milling tank, filling with an inert gas can effectively prevent the oxide from being further oxidized. Additionally, to further avoid the oxide from being further oxidized, vacuum pumping can be carried out before filling with the inert gas and then filling with the inert gas, which can avoid the residual oxygen and prevent the heat generated during the ball milling process from causing the raw materials to react in an oxygen environment.

[0021] Preferably, in the above method, the single continuous ball milling time does not exceed 30 minutes, preferably 10 - 30 minutes, and the room temperature cooling is not less than 10 minutes, preferably 10 - 30 minutes.

[0022] Preferably, in the above method, the cumulative ball milling time of the ball milling in step S1 is 2 - 10 h. During the ball milling process, the grinding balls collide and generate heat. Long-term continuous ball milling will cause the overall temperature in the ball milling tank to be too high, affecting the performance of the material.

[0023] Preferably, in the above method, the ball milling method adopted is planetary ball milling, the ball mill speed is 300-1000RPM, the ball milling time is 6-8 hours, and the intermittent operation mode is adopted, the single operation time is 20min, and the intermittent operation time is 10min.

[0024] Preferably, in the above method, plasma assistance is also required during ball milling in step S1, specifically, when the sodium source, nickel source, iron source, manganese source, zinc source and copper source are placed in the ball milling device, vacuum is first evacuated, then inert gas is filled, and then the inert gas is ionized into plasma and ball milling is performed. Plasma is widely used in material processing. The extremely high electron energy and electron density of plasma, as well as the highly active particles in the excited state that impact the exposed material surface, can not only serve as a heat source, but also induce a series of physical and chemical reactions, thereby changing the structure, composition, group and wettability of the material surface.

[0025] Further preferably, in the above method, in the case of plasma-assisted ball milling, the relative pressure of the ball milling tank of the ball milling device is 0.01-10 MPa. In the present invention, plasma is a quasi-neutral gas that exhibits collective behavior and is composed of a large number of positively and negatively charged particles, electrons and neutral particles, and free radicals generated during the discharge process of the gas. Therefore, in the case of plasma-assisted ball milling, the pressure in the ball milling tank needs to be maintained at a negative pressure.

[0026] Plasma is a quasi-neutral gas that produces a large number of positively and negatively charged particles, electrons, neutral particles and free radicals during the discharge process and exhibits collective behavior. Among them, low-temperature plasma is widely used in material processing. The extremely high electron energy and electron density of plasma, as well as the highly active particles in the excited state, impact the exposed material surface, which can not only serve as a heat source, but also induce a series of physical and chemical reactions, thereby changing the structure, composition, group and wettability of the material surface.

[0027] Further preferably, in the above method, in the case of plasma-assisted ball milling, the rotation speed of the ball mill of the ball milling device is 700-1000RPM, and further preferably 750-950RPM.

[0028] Further preferably, in the above method, in the case of plasma-assisted ball milling, the discharge current of the plasma device is 1-2 A. In the case of plasma assistance, if the discharge current is too high, the ball milling jar may be broken down, and if it is too low, the effect is not good.

[0029] Further preferably, in the above method, in the absence of plasma-assisted ball milling, the rotation speed of the ball mill of the ball milling device is 300-700 RPM, and further preferably 350-550 RPM.

[0030] Specifically, in the case of plasma-assisted ball milling, the specific process of step S1 is to load the sodium source, nickel source, iron source, manganese source, zinc source and copper source into a ball milling jar, then evacuate the jar, then fill it with inert gas and ionize the inert gas into plasma, and then ball mill it in a plasma atmosphere to obtain a first mixture precursor.

[0031] Preferably, in the above method, the first mixture precursor is pressed into a tablet before the first heating of the first mixture precursor in step S2. The tablet pressing process is a conventional process, and the specific operation is also well known in the art.

[0032] For example, the specific operation of the tableting process is: pressing a disc with a diameter of 16 mm, applying a pressure of 10 MPa and maintaining the pressure for 1 minute to complete the tableting.

[0033] In the present invention, tableting is performed, which, on the one hand, reduces the porosity between the raw materials. There are a large number of gaps between the particles of the powder material in the natural state. Tableting can make the powder particles close to each other and rearrange, and the air is discharged, thereby effectively reducing the porosity of the green body. On the other hand, it can promote material transfer. In the subsequent sintering process, the transfer of materials (such as atomic diffusion, etc.) is a key step. After tableting, the distance between the particles of the green body is shortened, the atomic diffusion path is shortened during sintering, and the diffusion rate is accelerated, which is conducive to sintering.

[0034] Preferably, in the above method, the conditions for the first heating in step S2 are: a heating rate of 3-7°C / min, a heating temperature of 200-550°C, and a heating duration of 3-8h.

[0035] Preferably, in the above method, crushing, grinding and tableting are performed before the second heating in step S3. In the present invention, crushing and tableting are performed again. On the one hand, this is to promote material migration during the sintering process. Tabletting shortens the distance between material particles. During high-temperature sintering, material migration processes such as the diffusion of atoms or ions are key to material densification. Atoms or ions need to diffuse between particles to achieve material densification. The shortened particle distance after tableting provides more favorable conditions for the diffusion of atoms or ions, which can accelerate the sintering process, enable the material to reach a densified state faster, and improve the sintering efficiency. On the other hand, it prevents component segregation. For a multi-component material system, tableting can also prevent component segregation. If the mixed powder is directly sintered at high temperature, since the powder particles of different components may have different sizes and densities, their fluidity at high temperatures is also different, which can easily lead to uneven distribution of components during the sintering process.

[0036] For example, before the second heating in step S3, the particles are crushed and ground to a particle size of less than 100 μm, and then the particles are pressed into a disc with a diameter of 16 mm at a pressure of 10 MPa for 1 minute, and the tableting is completed.

[0037] Preferably, in the above method, the conditions for the second heating in step S3 are: a heating rate of 3-7°C / min, a heating temperature of 800-950°C, and a heating duration of 12-24h.

[0038] The method of the present invention adopts two-stage sintering, wherein the first stage of sintering is a low-temperature insulation stage, and the second stage is a high-temperature insulation stage. On the one hand, the first stage of low-temperature insulation eliminates adsorbed gas and moisture. The raw material powder will adsorb a certain amount of gas and moisture during storage and processing. These adsorbed gas and moisture can be effectively removed at this stage to avoid the destruction of the material structure due to the rapid expansion of gas during high-temperature sintering. At the same time, for materials containing crystal water, low-temperature insulation can gradually remove the crystal water to prevent the material from cracking due to the sudden release of crystal water at the high-temperature stage; on the other hand, the material structure is preliminarily homogenized. Low-temperature insulation can make the distribution of components inside the material more uniform. Since the material has not been completely sintered at this stage, there is a certain fluidity between the particles. The components in the material can be preliminarily diffused and evenly distributed at this stage, which helps to obtain materials with more uniform performance in the subsequent high-temperature sintering stage. There are three functions in the high-temperature insulation stage: the first function is to achieve densification. High-temperature insulation (usually above a certain proportion of the melting point of the material, such as about 0.7-0.9 times the melting point for metal materials) is the key stage of material sintering. At this stage, the material particles are fully combined through mechanisms such as atomic diffusion, which greatly reduces the porosity of the material and significantly increases the density; the second function is to form a stable crystal structure and phase. During the high-temperature insulation process, the material can form a stable crystal structure and phase. For example, in the sintering of some composite materials, high temperature can promote reactions between different components to form new compound phases or stable solid solution phases. The formation of these new phases is crucial to improving the performance of the material (such as strength, hardness, conductivity, etc.). For example, a certain sintering temperature is required in the present invention to form a stable crystal structure; the third function is to optimize the material performance. This stage can optimize other properties of the material such as mechanical properties. Obviously, the double-stage sintering of the present invention is crucial to the performance of the high-entropy layered positive electrode material of the sodium ion battery of the present invention.

[0039] Preferably, in the above method, the sodium source, nickel source, iron source, manganese source, zinc source and copper source refer to compounds for providing Na, Ni, Fe, Mn, Zn and Cu, and there is no particular restriction on their types, which can be selected according to actual needs. Exemplarily, the sodium source includes but is not limited to a mixture of any one or more of sodium carbonate, sodium hydroxide, sodium nitrate and sodium acetate, and the remaining nickel source, iron source, manganese source, zinc source and copper source are selected from a mixture of one or more of oxides, acetates or nitrates of the corresponding metals.

[0040] In addition, it is relatively easy to understand that in step S, the amount of the sodium source, nickel source, iron source, manganese source, zinc source and copper source is calculated according to the molar ratio of each metal raw material in the final sodium ion battery high entropy layered positive electrode material to be obtained, that is, the molar ratio of the sodium content in the sodium source, the nickel content in the nickel source, the iron content in the iron source, the manganese content in the manganese source, the zinc content in the zinc source and the copper content in the copper source is ensured to meet the final product NaNi x Fe y Mn z Zn m Cu p The molar ratio of each metal element in O2, where 0 <x<1,0<y<1,0<z<1,0<m,p<0.1。

[0041] In a third aspect of the present invention, a positive electrode sheet for a sodium ion battery is provided, wherein the positive electrode sheet contains the above-mentioned high-entropy layered positive electrode material for a sodium ion battery.

[0042] Preferably, the positive electrode sheet comprises a positive electrode current collector and a positive electrode sheet layer arranged on the positive electrode current collector, the positive electrode sheet layer comprises a positive electrode active material and a binder, and the positive electrode active material comprises the above-mentioned sodium ion battery high entropy layered positive electrode material.

[0043] Further preferably, the mass proportion of the above-mentioned sodium ion battery high entropy layered positive electrode material in the positive electrode material layer can be greater than or equal to 60wt%, for example, 70-80%, 80%-90%, 75% and the like.

[0044] Still more preferably, the positive electrode material layer may also include a conductive agent.

[0045] In the above-mentioned positive electrode sheet, the positive electrode current collector is conventional in the art, and further preferably, the positive electrode current collector includes but is not limited to metal foil or alloy foil, and its surface can be etched or roughened to form a secondary structure to facilitate effective contact with the positive electrode material layer. An exemplary metal foil can be aluminum foil.

[0046] In the above-mentioned positive electrode plate, the amount and type of the binder and the conductive agent are conventional amounts and types in the art. For example, the binder may specifically include but is not limited to one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), lithium polyacrylate (Li-PAA), polyacrylate, polyacrylamide (PAM), polyimide (PI), etc.; the conductive agent may specifically include but is not limited to one or more of acetylene black, Ketjen black, SupperP conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers, Super C65 and single-walled carbon nanotubes (SWCNT), etc.

[0047] In addition, in the positive electrode plate of the present invention, the positive electrode active material may also include other conventional positive electrode active components in the art, such as Prussian blue compounds (such as sodium ferrocyanide, nickel ferrocyanide), polyanionic compounds, sodium iron phosphate (NaFePO4), sodium vanadium fluorophosphate, layered oxides: sodium nickel iron manganese oxide, etc.

[0048] Other positive electrode active components can be dispersed together with the above-mentioned sodium ion battery high entropy layered positive electrode material of the present invention in the positive electrode material layer. The two can exist independently or in the form of a composite material.

[0049] The positive electrode plate of the present invention uses the above-mentioned sodium ion battery high entropy layered positive electrode material of the present invention, and has good cycle stability when used in sodium ion batteries.

[0050] In a fourth aspect of the present invention, a method for preparing the positive electrode sheet for the above-mentioned sodium ion battery is provided, which comprises the following steps:

[0051] SF1 prepares positive electrode slurry: positive electrode active material, binder, and optional conductive agent are uniformly mixed in a solvent to prepare positive electrode slurry;

[0052] SF2 coating of positive electrode slurry: The positive electrode slurry prepared in step SF1 is coated on the positive electrode current collector, and then dried to obtain a positive electrode sheet for a sodium ion battery.

[0053] Obviously, the preparation method of the present invention is simple, easy to implement, and can be prepared on a large scale, wherein the method of preparing the positive electrode slurry in step SF1 is a conventional method in the art, such as preparing the slurry by a high-speed stirring degassing machine.

[0054] Preferably, the solvent used in step SF1 is water, an alcohol solvent, an amide solvent, an ether solvent or the like, and the amount used is also the amount used in the art.

[0055] Further preferably, the positive electrode active material includes the above-mentioned sodium ion battery high entropy layered positive electrode material of the present invention and other optional positive electrode active components, and other positive electrode active components are exemplified by Prussian blue compounds (such as sodium ferrocyanide, nickel ferrocyanide), polyanionic compounds, sodium iron phosphate (NaFePO4), fluorovanadium phosphate, sodium layered oxide: sodium nickel iron manganate, etc. Further preferably, in the positive electrode material layer formed by coating the above-mentioned positive electrode slurry on the positive electrode current collector, the mass percentage of the positive electrode active material to the positive electrode material layer is greater than or equal to 60wt%, and further preferably, the mass percentage of the high entropy layered positive electrode material of the sodium ion battery of the present invention to the positive electrode material layer is greater than or equal to 60wt%, for example, 70-80%, 80%-90%, 75%, etc.

[0056] In the above method, the positive electrode current collector is conventional in the art, and further preferably, the positive electrode current collector includes but is not limited to metal foil or alloy foil, the surface of which can be etched or roughened to form a secondary structure to facilitate effective contact with the positive electrode material layer. An exemplary metal foil can be aluminum foil.

[0057] In the above method, the amount and type of the binder and the conductive agent are conventional amounts and types in the art, such as the binder may specifically include but not limited to one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), lithium polyacrylate (Li-PAA), polyacrylate, polyacrylamide (PAM), polyimide (PI), etc. The conductive agent may specifically include but not limited to one or more of acetylene black, Ketjen black, SupperP conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers, Super C65 and single-walled carbon nanotubes (SWCNT), etc.

[0058] Preferably, in the above method, in the step SF1, the mass ratio of the positive electrode active material, the binder, and the conductive agent is (7.5-8.5): (0.75-1.25): (0.75-1.25). At this ratio, the positive electrode plate has good cycle stability when applied to sodium ion batteries.

[0059] Preferably, in the above method, in the step SF2, the positive electrode slurry prepared in the step SF1 is coated on the positive electrode current collector to a thickness of 100 μm to 250 μm.

[0060] Preferably, in the above method, in step SF2, the positive electrode current collector coated with the positive electrode slurry is dried by a conventional drying method in the art, such as oven drying, air drying, etc., and there is no strict limitation, as long as the purpose can be achieved.

[0061] In a fifth aspect of the present invention, a sodium ion battery made using the above-mentioned positive electrode plate is provided, which includes the above-mentioned positive electrode plate.

[0062] The shape of the battery of the present invention is not particularly limited, and can be cylindrical, button (coin), flat, square, etc. It can be used in conventional terminal consumer products such as mobile phones, computers, watches, etc.

[0063] Compared with the prior art, the high entropy layered cathode material for sodium ion batteries of the present invention achieves good electrochemical performance, especially excellent cycle performance, by regulating the ratio of the elements Ni, Fe, Mn, Zn, and Cu. In addition, the present invention can efficiently prepare the above-mentioned material having good electrochemical performance, especially excellent cycle performance, by regulating the ratio of the elements Ni, Fe, Mn, Zn, and Cu only through simple ball milling and two heating methods. In addition, the preparation process is simple and controllable, the raw material source is abundant and the cost is low, which can provide a basis for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 X-ray diffraction spectra of materials prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention;

[0065] Figure 2 This is a scanning electron microscope image of the high entropy layered cathode material for sodium ion batteries prepared in Example 1;

[0066] Figure 3 This is a scanning electron microscope image of the high entropy layered cathode material for a sodium ion battery prepared in Example 2;

[0067] Figure 4 This is a scanning electron microscope image of the sodium ion battery positive electrode material prepared in Comparative Example 1;

[0068] Figure 5 This is a scanning electron microscope image of the sodium ion battery positive electrode material prepared in Comparative Example 2;

[0069] Figure 6 This is a scanning electron microscope image of the sodium ion battery positive electrode material prepared in Comparative Example 3;

[0070] Figure 7 This is a scanning electron microscope image of the sodium ion battery positive electrode material prepared in Comparative Example 4;

[0071] Figure 8 The charge-discharge cycle diagrams of the materials obtained in Example 1, Comparative Example 1 and Comparative Example 3;

[0072] Fig. 9 The charge and discharge cycle diagrams of the materials prepared in Example 2, Comparative Example 2, and Comparative Example 4 are shown. DETAILED DESCRIPTION

[0073] In order to more clearly illustrate the specific implementation of the present invention or the technical solution in the prior art, the specific implementation will be explained below in conjunction with the drawings used as needed.

[0074] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0075] The raw materials used in the following examples are all commercially available.

[0076] Example

[0077] Example 1

[0078] A Preparation of high entropy layered cathode materials for sodium ion batteries

[0079] S1. 2.0424g sodium carbonate (Na2CO3), 0.6621g nickel oxide (NiO), 1.0154g iron oxide (Fe2O3), 0.9700g manganese tetraoxide (Mn3O4), 0.1568g zinc oxide (ZnO) and 0.1533g copper oxide (CuO) (wherein the molar ratio of each metal element is 1.00:0.23:0.33:0.33:0.05:0.05) are loaded into a planetary ball mill, and then sealed and canned under argon protection for ball milling, wherein the ball mill is loaded with zirconium oxide grinding balls with a mass ratio of 20:1 to the raw material, and the ball milling parameters are set as follows: the working mode is "intermittent operation, timed shutdown" mode, the rotation speed of the planetary ball mill is 400RPM, the total operation time is 6h, wherein the single operation time is 20min, and the intermittent operation time is 10min, which is used as a cycle to obtain the first mixture precursor;

[0080] S2: pressing the first mixture precursor obtained in step S1 into a disc with a diameter of 16 mm at a pressure of 10 MPa, and maintaining the pressure for 1 minute, then placing the obtained pressed disc into an alumina porcelain boat and performing a first heating calcination at 500° C. for 6 hours, wherein the heating rate from room temperature to 500° C. is 5° C. / min, to obtain a second mixture precursor;

[0081] S3. The second mixture precursor obtained in step S2 is crushed and ground to a particle size that can pass through a 200-mesh sieve, and then pressed into a 16 mm diameter disc at a pressure of 10 MPa, and the pressure is maintained for 1 minute, and then put back into an alumina porcelain boat and heated and calcined for a second time at 900°C for 24 hours, wherein the heating rate from room temperature to 900°C is 5°C / min, to obtain a sodium ion battery high entropy layered positive electrode material, denoted as A1, whose chemical formula is NaNi 0.23 Fe 0.33 Mn 0.33 Cu 0.05 Zn 0.05 O2.

[0082] Figure 1The X-ray diffraction pattern of A1 prepared in this example is compared with that of the typical O3-type material NaNi 0.5 Mn 0.5 The XRD spectrum peaks of the crystal structure of O2 (NO.054-0887) are compared. It can be clearly seen from the figure that the characteristic peaks of A1 are the characteristic peaks of O3 type layered materials, both corresponding to the R-3m group space group of the O3 type layered structure. Figure 2 This is the image of A1 prepared in this example under a scanning electron microscope.

[0083] B Preparation of positive electrode for sodium ion battery

[0084] SF1 prepares positive electrode slurry: 0.4g of the above-prepared A1, 0.05g of binder (polyvinylidene fluoride PVDF) and 0.05g of conductive agent (Super C65) are uniformly mixed, and 1.3g of N-methylpyrrolidone (NMP) is used as solvent to prepare positive electrode slurry through a high-speed stirring degassing machine;

[0085] SF2 coated positive electrode slurry: The prepared positive electrode slurry was evenly coated on the battery-grade aluminum foil with a coating thickness of 160 μm. After drying in a vacuum drying oven at 80 ° C for 10 hours to completely remove NMP, the positive electrode sheet was obtained by punching a 12 mm disc; the A1 active material loading was about 3 mg / cm 2 .

[0086] C. Prepare the prepared positive electrode sheet into a button battery and conduct electrochemical performance test

[0087] SC1 prepares the isolation film: punch out 19mm glass fiber as the isolation film, and the isolation film needs to be dried in a vacuum oven to remove residual moisture;

[0088] SC2 Preparation of button-type CR2025 half-cell: This step needs to be carried out in a glove box filled with argon and with a water and oxygen content of less than 0.01ppm. The positive electrode sheet, the isolation membrane and the commercially available negative electrode sheet are assembled in order, and the electrolyte is used to fully infiltrate them respectively, and then assembled into a button-type CR2025 half-cell. The electrolyte used is: a solution formed by sodium perchlorate with a concentration of 1 mol / L in a mixed solvent of ethylene carbonate and propylene carbonate with a volume ratio of 1:1, and 10% by mass of fluoroethylene carbonate is added;

[0089] SC3 electrochemical performance test: The button CR2025 half-cell prepared by SC2 was subjected to constant current charge and discharge tests at room temperature under the following conditions in the LAND CT2001A battery testing system: the test was carried out using the specific capacity test method, at 30°C, the cell was charged to 4.0V at a 4C constant current, and the charge specific capacity at this time was recorded; the cell was then discharged to 2.0V at a 4C constant current, and the discharge specific capacity at this time was recorded.

[0090] Example 2

[0091] A Preparation of high entropy layered cathode materials for sodium ion batteries

[0092] S1. 2.0424 g of sodium carbonate (Na2CO3), 0.6621 g of nickel oxide (NiO), 1.0154 g of iron oxide (Fe2O3), 0.9700 g of manganese tetraoxide (Mn3O4), 0.1568 g of zinc oxide (ZnO) and 0.1533 g of copper oxide (CuO) (wherein the molar ratio of each metal element is 1.00:0.23:0.33:0.33:0.05:0.05)) are loaded into a planetary ball mill, and then sealed and filled under argon protection for ball milling, wherein the ball mill is loaded with tungsten carbide grinding balls in a mass ratio of 20:1 to the raw materials, and then the ball mill is operated by operating the vacuum valve. The inside of the tank is evacuated and filled with argon gas with a relative pressure of 0.1 MPa so that the pressure of argon gas in the ball mill tank is 0.1 MPa. Finally, the ball mill tank is installed and fixed on a ball mill, the model of the ball mill is Plasma-BM-L, the power is turned on and the ball mill is started for ball milling and the plasma device is started, wherein the discharge current of the plasma device is 2A, and the ball milling parameters are set as follows: the working mode is "intermittent operation, timed shutdown" mode, the speed of the ball mill is 800RPM, the total operation time is 3h, wherein the single operation time is 20min, and the intermittent operation time is 10min, which is taken as a cycle to obtain the first mixture precursor;

[0093] S2: pressing the first mixture precursor obtained in step S1 into a disc with a diameter of 16 mm at a pressure of 10 MPa, and maintaining the pressure for 1 minute, then placing the obtained pressed disc into an alumina porcelain boat and performing a first heating calcination at 500° C. for 6 hours, wherein the heating rate from room temperature to 500° C. is 5° C. / min, to obtain a second mixture precursor;

[0094] S3. The second mixture precursor obtained in step S2 is crushed and ground to a particle size that can pass through a 200-mesh sieve, and then pressed into a disc with a diameter of 16 mm at a pressure of 10 MPa, and the pressure is maintained for 1 minute, and then put back into an alumina porcelain boat and heated and calcined for a second time at 900° C. for 24 hours, wherein the heating rate from room temperature to 900° C. is 5° C. / min, to obtain a sodium ion battery high entropy layered positive electrode material, denoted as A2, whose chemical formula is NaNi0.23 Fe 0.33 Mn 0.33 Cu 0.05 Zn 0.05 O2.

[0095] Figure 1 The X-ray diffraction pattern of A2 prepared in this embodiment is compared with that of the typical O3-type material NaNi 0.5 Mn 0.5 The XRD spectrum peak types of the crystal structure of O2 (NO.054-0887) were compared. It can be clearly seen from the figure that the characteristic peaks of A2 are the characteristic peaks of O3 type layered materials, both corresponding to the R-3m group space group of the O3 type layered structure. Figure 3 This is the image of A2 prepared in this example under a scanning electron microscope. It can be seen from the figure that the samples are all block-shaped irregular particles with a size between 4-10μm. Plasma-assisted ball milling does not significantly change the surface morphology of the material and can maintain the integrity of the particles.

[0096] B Preparation of positive electrode for sodium ion battery

[0097] The positive electrode sheet for the sodium ion battery of this embodiment is prepared in the manner described in Example 1, with the only difference being that the positive electrode material used is the sodium ion battery high entropy layered positive electrode material A2 prepared in this embodiment.

[0098] C. Prepare the prepared positive electrode sheet into a button battery and conduct electrochemical performance test

[0099] The positive electrode sheet prepared in this example was formed into a button cell in the manner described in Example 1 and the electrochemical performance was tested.

[0100] Comparative Example

[0101] Comparative Example 1

[0102] A Preparation of positive electrode materials for sodium ion batteries

[0103] The positive electrode material for the sodium ion battery of this comparative example was prepared in the manner described in Example 1, except that no copper source was added, that is, 2.0462 g of sodium carbonate (Na2CO3), 0.8075 g of nickel oxide (NiO), 1.0173 g of iron oxide (Fe2O3), 0.9718 g of manganese tetraoxide (Mn3O4), and 0.1571 g of zinc oxide (ZnO) (wherein the molar ratio of each metal element was 1.00:0.28:0.33:0.33:0.05) were used to prepare the positive electrode material for the sodium ion battery. The obtained product was recorded as B1, and its chemical formula was NaNi 0.28 Fe 0.33 Mn 0.33 Zn 0.05 O2.

[0104] B Preparation of positive electrode for sodium ion battery

[0105] The positive electrode sheet for the sodium ion battery of this comparative example was prepared in the manner described in Example 1, with the only difference being that the positive electrode material used was the positive electrode material B1 prepared in this comparative example.

[0106] C. Prepare the prepared positive electrode sheet into a button battery and conduct electrochemical performance test

[0107] The positive electrode sheet prepared in this comparative example was formed into a button cell in the manner described in Example 1 and the electrochemical performance was tested.

[0108] Comparative Example 2

[0109] A Preparation of positive electrode materials for sodium ion batteries

[0110] The positive electrode material for the sodium ion battery of this comparative example was prepared in the manner described in Example 2, except that no copper source was added, that is, 2.0462 g of sodium carbonate (Na2CO3), 0.8075 g of nickel oxide (NiO), 1.0173 g of iron oxide (Fe2O3), 0.9718 g of manganese tetraoxide (Mn3O4), and 0.1571 g of zinc oxide (ZnO) (wherein the molar ratio of each metal element was 1.00:0.28:0.33:0.33:0.05) were used to prepare the positive electrode material for the sodium ion battery. The obtained product was recorded as B2, and its chemical formula was NaNi 0.28 Fe 0.33 Mn 0.33 Zn 0.05 O2.

[0111] B Preparation of positive electrode for sodium ion battery

[0112] The positive electrode sheet for the sodium ion battery of this comparative example was prepared in the manner described in Example 1, with the only difference being that the positive electrode material used was the positive electrode material B2 prepared in this comparative example.

[0113] C. Prepare the prepared positive electrode sheet into a button battery and conduct electrochemical performance test

[0114] The positive electrode sheet prepared in this comparative example was formed into a button cell in the manner described in Example 1 and the electrochemical performance was tested.

[0115] Comparative Example 3

[0116] A Preparation of positive electrode materials for sodium ion batteries

[0117] The positive electrode material for the sodium ion battery of this comparative example was prepared in the manner described in Example 1, except that no zinc source and copper source were added, that is, 2.0406 g of sodium carbonate (Na2CO3), 0.9577 g of nickel oxide (NiO), 1.0238 g of iron oxide (Fe2O3), and 0.9799 g of manganese tetraoxide (Mn3O4) (wherein the molar ratio of each metal element was 1.00:0.33:0.33:0.33) were used to prepare the positive electrode material for the sodium ion battery. The obtained product was recorded as B3, and its chemical formula was NaNi 0.33 Fe 0.33 Mn 0.33 O2.

[0118] B Preparation of positive electrode for sodium ion battery

[0119] The positive electrode sheet for the sodium ion battery of this comparative example was prepared in the manner described in Example 1, with the only difference being that the positive electrode material used was the positive electrode material B3 prepared in this comparative example.

[0120] C. Prepare the prepared positive electrode sheet into a button battery and conduct electrochemical performance test

[0121] The positive electrode sheet prepared in this comparative example was formed into a button cell in the manner described in Example 1 and the electrochemical performance was tested.

[0122] Comparative Example 4

[0123] A Preparation of positive electrode materials for sodium ion batteries

[0124] The positive electrode material for the sodium ion battery of this comparative example was prepared in the manner described in Example 2, except that no zinc source and copper source were added, that is, 2.0406 g of sodium carbonate (Na2CO3), 0.9577 g of nickel oxide (NiO), 1.0238 g of iron oxide (Fe2O3), and 0.9799 g of manganese tetraoxide (Mn3O4) (wherein the molar ratio of each metal element was 1.00:0.33:0.33:0.33) were used to prepare the positive electrode material for the sodium ion battery. The obtained product was recorded as B4, and its chemical formula was NaNi 0.33 Fe 0.33 Mn 0.33 O2.

[0125] B Preparation of positive electrode for sodium ion battery

[0126] The positive electrode sheet for the sodium ion battery of this comparative example was prepared in the manner described in Example 1, with the only difference being that the positive electrode material used was the positive electrode material B4 prepared in this comparative example.

[0127] C. Prepare the prepared positive electrode sheet into a button battery and conduct electrochemical performance test

[0128] The positive electrode sheet prepared in this comparative example was formed into a button cell in the manner described in Example 1 and the electrochemical performance was tested.

[0129] Test Example

[0130] Test Example 1 Physical Properties Test Analysis

[0131] The sodium ion battery high entropy layered positive electrode materials A1 and A2 prepared in Examples 1 and 2 and the sodium ion battery positive electrode materials B1-B4 prepared in Comparative Examples 1-4 were subjected to X-ray test structure and scanning electron microscope morphology observation, and the results are shown in Figure 1 and Figure 2-7 middle.

[0132] Figure 1 The X-ray diffraction patterns of various embodiments and comparative examples are given and compared with those of the typical O3-type material NaNi 0.5 Mn 0.5 The XRD spectrum peaks of the crystal structure of O2 (NO.054-0887) are compared. It can be clearly seen from the figure that they all have characteristic peaks of O3-type layered materials, corresponding to the R-3m group space group of the O3-type layered structure. Figure 2-7 It can be seen that the products obtained in each embodiment and comparative example are block-shaped irregular particles with a size between 4-10 μm, and Figure 2 and Figure 3 , Figure 4 , Figure 6 In comparison, it can be explained that plasma treatment, Cu, Zn co-doping, etc. did not change the surface morphology of the material, and the material still maintained lamellar particles.

[0133] Test Example 2 Electrochemical Performance Test Analysis

[0134] The electrochemical performance test results of the sodium ion battery prepared by the high entropy layered positive electrode materials of Examples 1 and 2 and the positive electrode materials prepared by Comparative Examples 1-4 are shown in Tables 1 and Figure 8-9 middle.

[0135] Table 1 Electrochemical performance test results

[0136]

[0137]

[0138] According to the specific implementation of the present invention, Example 1, Comparative Example 1 and Comparative Example 3 are positive electrode materials for sodium ion batteries prepared by planetary ball milling; while Example 2, Comparative Example 2 and Comparative Example 4 are positive electrode materials for sodium ion batteries prepared by plasma-assisted ball milling. 0.28Fe 0.33 Mn 0.33 Zn 0.05 O2 and 1-NaNi in Comparative Example 3 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material, the sodium ion battery layered high entropy positive electrode material prepared in Example 1 of the present invention has a more excellent cycle performance. After 150 cycles of 4C charge and discharge, it can still maintain 84.31% of the discharge capacity, while the comparative examples 1 and 3 are only 73.29% and 18.54% respectively. Compared with 2-NaNi in comparative example 2 0.28 Fe 0.33 Mn 0.33 Zn 0.05 O2 and 2-NaNi in Comparative Example 4 0.33 Fe 0.33 Mn 0.33 The positive electrode material of O2, the layered high entropy positive electrode material of sodium ion battery prepared in Example 2 of the present application has a more excellent cycle performance. After 150 cycles of 4C charge and discharge, it can still maintain 84.09% of the discharge specific capacity, while the comparative example 2 and comparative example 4 are only 73.06% and 27.64% respectively. In summary, the high entropy positive electrode materials prepared by the two preparation methods of the present invention have achieved significant improvement in performance.

[0139] The above examples and comparative examples specifically demonstrate the universality and effectiveness of the electrochemical performance improvement of the sodium ion layered battery positive electrode material prepared by the present invention from three aspects, namely, different material components, different contents, and different preparation methods. This is unique in achieving the rapid transfer of sodium ions in the lattice, and ultimately achieving the improvement of ionic conductivity and battery performance.

[0140] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs may also make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the invention should also fall within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A high entropy layered cathode material for a sodium ion battery, characterized in that: Chemical formulaNaNi x Fe y Mn z Zn m Cu p O2, where 0 <x<1,0<y<1,0<z<1,0<m,p<0.1。 2. The sodium ion battery high entropy layered cathode material according to claim 1, characterized in that The high entropy layered cathode material for sodium ion batteries belongs to the hexagonal crystal system and has a space group of R-3m. Further preferably, the high entropy layered cathode material for sodium ion batteries is an O3 type layered structure with a space group of R-3m.

3. A method for preparing the high entropy layered cathode material for sodium ion batteries according to claim 1 and / or 2, characterized in that: The following steps are involved: S1. ball milling a sodium source, a nickel source, an iron source, a manganese source, a zinc source and a copper source under an inert atmosphere to obtain a first mixture precursor; S2. heating the first mixture precursor obtained in step S1 for the first time to obtain a second mixture precursor; S3. The second mixture precursor obtained in step S2 is crushed and heated for the first time to obtain a high-entropy layered positive electrode material for a sodium ion battery.

4. The method according to claim 3, characterized in that The ball milling process needs to be carried out under an inert gas, and the inert gas is one or more of high-purity nitrogen, argon, and helium.

5. The method according to claim 3, characterized in that: The grinding balls used in the ball mill are zirconium balls, tungsten carbide grinding balls and / or stainless steel balls, and the ball-to-material ratio can be (10-30):

1.

6. The method according to claim 3, characterized in that When ball milling is performed in step S1, plasma assistance is also required. Specifically, when the sodium source, nickel source, iron source, manganese source, zinc source and copper source are placed in the ball milling device, vacuum is first evacuated, then inert gas is filled in, and then the inert gas is ionized into plasma and ball milling is performed.

7. The method according to claim 6, characterized in that In the case of plasma-assisted ball milling, the rotation speed of the ball mill of the ball milling device is 700-1000 RPM, and more preferably 750-950 RPM.

8. A positive electrode sheet for a sodium ion battery, characterized in that: The positive electrode sheet contains the sodium ion battery high entropy layered positive electrode material according to claim 1 and / or 2.

9. A method for preparing the positive electrode sheet for a sodium ion battery according to claim 8, characterized in that: The positive electrode sheet contains the sodium ion battery high entropy layered positive electrode material according to claim 1 and / or 2.

10. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • High-entropy boride ceramic material and preparation method thereof

    CN110606749A

  • O3-phase high-entropy layered metal oxide and preparation method and application thereof

    CN115064693A

  • High-entropy compound for positive electrode of zinc ion battery and preparation method of high-entropy compound

    CN115084501A

  • Preparation method of high-entropy oxide sodium ion battery positive electrode material

    CN115207341A

  • Cobalt-free high-entropy oxide sodium battery positive electrode material as well as preparation method and application thereof

    CN117059793A

Cited By

  • Layered oxide material and preparation method thereof, positive electrode material, positive electrode plate and sodium ion battery

    CN121617948A

  • Layered oxide material, method for producing the same, positive electrode material, positive electrode sheet, sodium-ion battery

    CN121617948B